The yoke and the law of discipline: On the intellectual background of the author of the minor legend of Stephen - B. Kovács, Péter (Verso – Irodalomtörténeti folyóirat, 2021)
It is well known to readers and researchers of Hungarian medieval literature that there are three extant legends about our state-founding ruler, St. Stephen. Research history traditionally considers these texts as the most important group of Latin hagiographic works representing the Hungarian saints of the Arpadian age; it is no coincidence that an infinite number of academic works discuss them. In my paper I discuss certain passages which suggest that previous opinions, according to which the author of the minor legend was among the most skilled and educated scribes of the turn of the twelfth century, are adequate, and his work cannot be separated from the wider political and intellectual context of its transcription, the Investiture Controversy. In my paper, I argue that the author of the Legenda minor is clearly committed to the Roman Church, and as such, the work reveals ultramontane tendencies.